2002
DOI: 10.1021/jf025713a
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Fraction of Milk:  Comparison between Purge and Trap and Solid Phase Microextraction Techniques

Abstract: The aim of this research was to validate the results obtained previously by purge and trap (PT) and to investigate the ability of solid phase microextraction (SPME), a more rapid and less expensive technique, to discriminate drinking milk subjected to different heat treatments (i.e., pasteurization, ultrahigh temperature, "in-bottle" sterilization) and produced at different factories. The data obtained by both methods were processed by multivariate statistical analysis. PT and SPME showed comparable repeatabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 27 publications
12
84
1
Order By: Relevance
“…The repeatability and limit of detection of the final optimised method are similar to those found with other SPME methods for the isolation of dairy volatiles. 12,14,19,22 The theory that a longer fibre coating would compensate for shorter extraction times in terms of extraction efficiency was shown to hold true for the compounds eluting prior to 2-heptanone. Figure 3 shows the recoveries of each analyte (50 µg l −1 milk) for the 15 and 30 min extractions at 40 • C using the 2 cm DVB/Carboxen/PDMS coating relative to the 60 min extraction at 40 • C using the 1 cm DVB/Carboxen/PDMS coating.…”
Section: Calibration Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The repeatability and limit of detection of the final optimised method are similar to those found with other SPME methods for the isolation of dairy volatiles. 12,14,19,22 The theory that a longer fibre coating would compensate for shorter extraction times in terms of extraction efficiency was shown to hold true for the compounds eluting prior to 2-heptanone. Figure 3 shows the recoveries of each analyte (50 µg l −1 milk) for the 15 and 30 min extractions at 40 • C using the 2 cm DVB/Carboxen/PDMS coating relative to the 60 min extraction at 40 • C using the 1 cm DVB/Carboxen/PDMS coating.…”
Section: Calibration Of Methodsmentioning
confidence: 99%
“…Headspace solid phase microextraction (SPME) offers a solvent-free, sensitive and reproducible alternative which is simple to conduct. In recent years, SPME has been applied to: the isolation of pentanal and hexanal from light-abused milk using a Carboxen/polydimethylsiloxane (Carboxen/PDMS)-coated fibre; 12 the analysis of microbial, lightinduced, copper-induced and heat-induced offflavours from milk using a Carboxen/PDMS-coated fibre; 13 the study of volatile compounds from pasteurised, UHT and in-bottle-sterilised milk using a divinylbenzene/Carboxen/polydimethylsiloxane (DVB /Carboxen/PDMS)-coated fibre; 14 and the analysis of various flavour compounds from reconstituted skim milk powder using a polydimethylsiloxane (PDMS)-coated fibre. 15 None of the above investigations reported a statistical comparison of different extraction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For both nitrogen analytical wavelengths, fair to good precision (correlation coefficients ranging from 0.984 to 0.995 Table 3 Sensibilities, S, in g g −1 (as defined in [24]), correlation coefficients r and detection limits LD in g g −1 for selected alkylpyrazines in cupuassu liquor using HS-SPME coupled to GC-AED and monitoring the 174 nm N emission line or 388 nm CN emission band when monitoring 174 nm and 0.989 to 0.998 for 388 nm) and adequate sensitivity and detectability were achieved. However, the line at 388 nm was chosen for quantitative applications due to its improved detectability (e.g.…”
Section: Quantification Of Alkylpyrazines In Cupuassu Liquor Using Thmentioning
confidence: 99%
“…In other hand, the higher sensitivity of dynamic headspace (HS) manipulation methods (specially when compared to SPME) accounts for their extense use to these samples [22,23]. However, even considering its lower sensitivity, in studies comparing both techniques for aroma analysis, performance of SPME has been found to be adequate [24,25]. Also, dynamic headspace procedures have some drawbacks [26], such as retention of water (when using carbon-based trapping materials), longer analysis time and possibility of degradation of trapped analytes when using thermal desorption.…”
Section: Introductionmentioning
confidence: 99%
“…Values are the mean of four replicates compounds (equilibration and sampling time). Equilibration times between 5 min and 1 h before SPME analysis have usually been reported in SPME analysis [9,19,20,21,22,23]. In this study, the effect of the homogenisation time before SPME sampling was studied using vials containing 5 mL olive brine that was stirred for 0, 10, 15, 30, 45 and 60 min before exposure of the fibre to the headspace.…”
Section: Sampling and Equilibration Timementioning
confidence: 99%